DYNAMICS OF ISLAMIC LEARNING DURING PANDEMIC TIMES AT SRIWIJAYA UNIVERSITY - Abdul Gafur; Nurhasan Nurhasan; Endang Switri; Apriyanti Apriyanti (Conciencia, 2021)
The focus of this research is to analyze how the implementation of Islamic Religious Education learning in the Technical Implementation Unit, Personality Development Course Sriwijaya University during the Covid-19 pandemic. This is because this pandemic condition requires educators to find the right formulation in learning process of Islamic religious education. The learning process used at this time is the online method, which has both positive and negative impacts. In the actualization of its implementation there are obstacles from both students and educators. The purpose of this study was to find out how the stages of implementing Islamic Religious Education learning consisting of Planning, Organizing, Actuating and Controlling/Evaluating, as well as to find out the obstacles of its implementation. The method used in this research is a qualitative research method. Where the data were collected through observation, interviews and documentation. The results showed that the learning activity was in accordance with the application of Islamic Religious Education learning management principles during the Covid-19 period. Nevertheless, the facilities needed in the online learning process still need improvement, such as the use of content in E-Learning and the use of B3. The problems encountered were sometimes caused by a lack of internet signal. The level of technological readiness from this research is expected to be able to answer the challenges of lecturers at Sriwijaya University in particular and in general in the world of other education.